Divining sugar substrates. (December 2018) - Schmid, Jochen
Scientists have combined functional and computational analysis to predict the substrate specificity of a family of glycosyltransferases fromArabidopsis thaliana, creating a tool that enables researchers to classify the donor and acceptor specificity of glycosyltransferase enzymes.